A study of heterogeneous traffic noise trigger parameters for urban areas - Lakawa, Irwan; Hujiyanto, Hujiyanto; Haryono, Haryono (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
So far, the review of the parameters that trigger traffic noise in urban areas has been partially based on only one factor, namely traffic flow. Meanwhile, other factors have not been included as variables that trigger traffic noise and the analysis has not been conducted simultaneously. In this research, the noise level was measured using a Sound Level Meter (SLM) and analyzed using a mathematical equation. The method for determining the parameters that trigger noise was analyzed through a simultaneous equation system using SmartPLS. The results of the study show that in big cities with heterogeneous traffic, the traffic composition is more dominated by motorcycles at 64%, followed by light vehicles at 32%, and heavy vehicles at 4% with an average vehicle speed of 36 km/h. The low speed is not due to traffic congestion but is mainly caused by driver behavior of not accelerating their vehicles. The parameters that can be used as indicators of heterogeneous traffic noise triggers in urban areas are traffic aspects with indicators of motorcycle volume and traffic density, road physical aspects with superelevation indicator, as well as environmental aspects of the road with the air temperature indicator.